2007
DOI: 10.12693/aphyspola.112.331
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Level Defects in MBE-Grown GaN-Based Laser Structure

Abstract: We present results of deep-level transient spectroscopy investigations of defects in a GaN-based heterostructure of a blue-violet laser diode, grown by plasma-assisted molecular beam epitaxy on a bulk GaN substrate. Three majority-carrier traps, T1 at E C − 0.28 eV, T2 at E C − 0.60 eV, and T3 at EV + 0.33 eV, were revealed in deep-level transient spectra measured under reverse-bias conditions. On the other hand, deep-level transient spectroscopy measurements performed under injection conditions, revealed one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The interface state density shows a broad peak centered at an energy which depends on the temperature. These energy values, ranging between 0.35 eV and 0.55 eV according to the temperature, are in good agreement with those obtained by Cho et al [35] (0.5-0.6 eV), Gotz et al [36] (0.49 eV), and Tsarova et al [37] (0.6 eV) using DLTS in GaN Schottky diodes, and are attributed to nitrogen anti-sites. These peaks can also originate from an unintentional surface oxidization which can occur during the fabrication process steps.…”
Section: Interface State Effectssupporting
confidence: 91%
“…The interface state density shows a broad peak centered at an energy which depends on the temperature. These energy values, ranging between 0.35 eV and 0.55 eV according to the temperature, are in good agreement with those obtained by Cho et al [35] (0.5-0.6 eV), Gotz et al [36] (0.49 eV), and Tsarova et al [37] (0.6 eV) using DLTS in GaN Schottky diodes, and are attributed to nitrogen anti-sites. These peaks can also originate from an unintentional surface oxidization which can occur during the fabrication process steps.…”
Section: Interface State Effectssupporting
confidence: 91%
“…The data points in plot, 1/C 2 verses applied reverse voltage V, are found approximately fit to a straight line, indicating junction as step junction [11]. However, a careful examination shows that two different straight lines can be fit in the voltage range 0-4.0 and 7-10 volts, which indicate that shallow level concentration on both p-and n-sides of the junction is nearly equal [9].…”
Section: Methodsmentioning
confidence: 99%
“…In earlier studies, Dyba et al [8] have detected two deep level traps in their metal-organic vapor-phase epitaxial (MOVPE)-grown GaN p-n junctions, while Tsarova et al [9] have observed four deep level defects in GaN-based laser structure grown by molecular-beam epitaxy (MBE). By employing DLTS, we report here nine deep levels in metal-organic chemical-vapor deposition (MOCVD)-grown InGaN PIN structure.…”
Section: Introductionmentioning
confidence: 99%
“…1/C 2 verses reverse bias plot is shown in Figure 1. Data was found to fit on two straight lines indicating almost uniform concentrations of acceptors and donors ( a N and d N ) in n and p sides of the PIN junction [16]. The concentrations were found to nearly same on both p and n sides of the junction.…”
Section: Measurementsmentioning
confidence: 87%